Family Controlling Shareholder and Financial Distress in Indonesia: Socio-Demographic Moderation - Fitria Fissamawati; Rayenda Khersna Brahmana; Giriati (Economics Development Analysis Journal, 2025)
Financial distress is a major issue for a company in terms of maintaining the sustainability of its performance in the future. One aspect that needs to be considered is the controlling shareholder family. It is an important factor that needs to be considered to see how the company's performance will develop in the future. Therefore, this study examines the relationship between the family controlling shareholders and the financial distress in Indonesia, which is moderated through socio-demographic factors. The moderated regression analysis (MRA) was applied to 253 Indonesian public limited companies from 2013 to 2021. The result revealed that family-controlling shareholders positively and significantly affect financial distress. On the other hand, experience as a socio-demographic factor also moderated this nexus negatively. Thus, the important role of the family controlling shareholders must be considered as a main factor for predicting financial distress in Indonesian companies.